TROPION-Lung10: a phase 3 study of datopotamab deruxtecan and rilvegostomig in patients with treatment-naïve locally advanced or metastatic nonsquamous non-small cell lung cancer with high PD-L1 expression and without actionable genomic alterations - Newsom-Davis, Thomas; Melosky, Barbara; Heist, Rebecca S.; Lu, Shun; Pasello, Giulia; Chen, Xiwei; Stachowiak, Marta; Lyfar, Pavlo; Forcina, Alessandra; Ramalingam, Suresh S. (Frontiers in Oncology, 2026)
BackgroundImmunotherapy targeting the programmed cell death (ligand)-1 (PD-[L]1) pathway has improved outcomes in patients with advanced/metastatic non-small cell lung cancer (NSCLC) without actionable genomic alterations (AGAs), especially those with high PD-L1 expression (≥50% of tumor cells [TC]). However, some patients have primary or acquired resistance to treatment and new therapeutic strategies are needed to address this. Datopotamab deruxtecan (Dato-DXd), a trophoblast cell surface antigen 2 (TROP2)-directed antibody–drug conjugate, and rilvegostomig, a bispecific anti-PD-1/anti-TIGIT antibody, have shown promising efficacy and manageable safety profiles in patients with advanced or metastatic NSCLC.Methods and designTROPION-Lung10 (NCT06357533) is a phase 3, open-label, multicenter, randomized study evaluating the efficacy and safety of first-line Dato-DXd plus rilvegostomig versus standard-of-care pembrolizumab in patients with advanced/metastatic nonsquamous NSCLC with PD-L1 TC expression ≥50% and without AGAs. Approximately 675 adults with nonsquamous stage IIIB/C or IV NSCLC not amenable to curative surgery or definitive chemoradiation, PD-L1 TC ≥50%, and no AGAs will be enrolled. Patients will be randomized (2:1:2) to receive Dato-DXd (6 mg/kg intravenously [IV] every 3 weeks [Q3W]) plus rilvegostomig (750 mg IV Q3W), rilvegostomig alone (750 mg IV Q3W), or pembrolizumab (200 mg IV Q3W for up to 35 cycles/24 months). The dual primary endpoints are progression-free survival (PFS) by blinded independent central review (BICR) per Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST v1.1) and overall survival (OS) in the TROP2 normalized membrane ratio (NMR) biomarker-positive population for Dato-DXd plus rilvegostomig versus pembrolizumab. The key secondary endpoints are PFS by BICR per RECIST v1.1 and OS in the full analysis set (FAS). Other secondary endpoints include the objective response rate and duration of response by BICR per RECIST v1.1, PFS2, patient-reported outcomes in the TROP2 NMR-positive population and FAS, and safety.DiscussionTROPION-Lung10 will assess first-line Dato-DXd plus rilvegostomig in patients with advanced/metastatic NSCLC with high PD-L1 expression and without AGAs.Clinical trial registrationClinicalTrials.gov, identifier NCT06357533.